The Logistics of a Dispersed Hotel - Pavić, Lazar (Interdisciplinary and Applied Konwledge for Green and Digital Logistics Processes, 2026)
This chapter addresses the issue of establishing the concept of a dispersed hotel grounded in the principles of sustainability, circular economy, and the reuse of pre-existing resources within a specific community. This represents a novel approach to the development of tourism activities in remote and rural areas, offering a solution to a multitude of challenges that may arise within the local environment. The chapter highlights the key advantages of the dispersed hotel as a tourism development concept when compared to the traditional hotel as an accommodation establishment. Furthermore, the chapter explores the various phases involved in the establishment of the dispersed hotel concept, among which the most pivotal phase can be identified as the concrete steps necessary for the implementation of the dispersed hotel concept within the local community.